Martin Luter wobec Sacrum Imperium - Wielomski, Adam (Dialogi Polityczne, 2019)
We have a great literature about theology and political thought of Martin Luther, but the researchers of his political thoughts do not see in his writings the theory of international relations. The aim of this text is the presentation my thesis that this theory exists. It result from Luther's thesis that the rebel princes of the Sacred Empire are not the rebellious lords counter the emperor, but the sovereign monarchs of sovereign states. This text shows the evolution of Luther's position in this matter. First, Luther acknowledges the right of princes to rebel only in religious matters, then against the imperial "tyranny" (the argument from the "ancient constitution"), and c. 1530 he considers them full sovereigns. Relations between the territorial sovereigns and the emperor are based on the "law of nature". This idea makes Luther predecessor of the theory of international relations of Thomas Hobbes.